Implementation Of An Occupational Safety And Health Management System At A Public Fuel Filling Station - Cahyana; Suroso; Flora Patricia Anggelia (International Journal of Management, Economic, Business and Accounting, 2024)
Purpose of the study — This study aims to describe the Occupational Safety and Health Management System at the Public Fuel Filling Station in Tamansari–Pangkalan Village and assess its compliance with Government Regulation Number 50 of 2012. Research method— A qualitative and descriptive approach was employed to understand and explain the implementation of the Occupational Safety and Health Management System in the specified work environment. Result— The research findings indicate that the Occupational Safety and Health Management System has been effectively implemented, successfully maintaining work safety and security. Key practices include the use of protective equipment, monitoring of working conditions, establishment of a safe environment, and safety training for workers. Conclusion— The Occupational Safety and Health Management System at the Public Fuel Filling Station in Tamansari–Pangkalan Village aligns with Government Regulation Number 50 of 2012. Future research is recommended to investigate factors contributing to vehicle fires at Fuel Filling Stations in the area.